The Effect Of Tuition Fees, Personal Selling Presenters And Reference Groups On College Decisions At The Indonesian Institute Of Business And Technology - Maisusanto, Eko; Willdahlia, Ayu Gede; Rahayu, Ni Made Astini; Sudianti , Ni Made (Sean Institute, 2025)
Education is an important pillar of Indonesia's development 2045 to improve the quality of human resources, so further education in higher education is a necessity in order to be able to compete and improve living standards. This study analyzes the effect of tuition fees, personal selling presenters, and reference groups on college decisions at the Indonesian Institute of Business and Technology Denpasar. By involving 176 students of class 2023 through proportional random sampling technique, the data were analyzed using multiple regression tests. The results show that partially and simultaneously, tuition fees, personal selling presenters, and reference groups have a positive and significant effect on college decisions. The results of this study indicate that: 1) Tuition partially has a positive and significant effect on college decisions. 2) Personal selling presenters partially have a positive and significant effect on college decisions. 3) The reference group partially has a positive and significant effect on college decisions. 4) Tuition fees, personal selling presenters, and reference groups have a joint (simultaneous) effect on college decisions.